Factors influencing engineering students for choosing techno-entrepreneurship as a career: An implication for better learning - Zachariah John Aviles Belmonte; Pamela Eyre Victoria R. Lira (International Journal of Evaluation and Research in Education (IJERE), 2023)
Techno-entrepreneurship is critical to the growth of society as a useful technique for overcoming youth unemployment. However, the growth of techno-entrepreneurship has been limited with the end outcome being less than satisfying. Hence, the purpose of this study was to determine the factors that influence the possibility of choosing techno-entrepreneurship as a profession among engineering students in the Philippines. There were 200 engineering students selected by stratified random sampling and the significance of the factors was then determined using Pearson correlation analysis. Based on the findings, students’ likelihood of choosing techno-entrepreneurship as a career was not influenced by their equipment availability but by their e-commerce experience, geographical location, and internet ability. This implies the need for academic personnel and instructors teaching techno-entrepreneurship courses to guarantee students have relevant technopreneur knowledge, skills, and competencies that value students’ creativity and innovation to encourage techno-entrepreneurship as a profession.